Resveratrol, sirtuins, and the promise of a DR mimetic - Baur, Joseph A. (Mechanisms of ageing and development, 2010)
Dietary restriction (DR) delays or prevents age-related diseases and extends lifespan in species ranging from yeast to primates. Although the applicability of this regimen to humans remains uncertain, a proportional response would add more healthy years to the average life than even a cure for cancer or heart disease. Because it is unlikely that many would be willing or able to maintain a DR lifestyle, there has been intense interest in mimicking its beneficial effects on health, and potentially longevity, with drugs. To date, such efforts have been hindered primarily by our lack of mechanistic understanding of how DR works. Sirtuins, NAD +-dependent deacetylases and ADP-ribosyltransferases that influence lifespan in lower organisms, have been proposed to be key mediators of DR, and based on this model, the sirtuin activator resveratrol has been proposed as a candidate DR mimetic. Indeed, resveratrol extends lifespan in yeast, worms, flies, and a short-lived species of fish. In rodents, resveratrol improves health, and prevents the early mortality associated with obesity, but its precise mechanism of action remains a subject of debate, and extension of normal lifespan has not been observed. This review summarizes recent work on resveratrol, sirtuins, and their potential to mimic beneficial effects of DR.